ANALISIS FAKTOR INTERNAL DAN EKSTERNAL SEBAGAI BAHAN PENYUSUN STRATEGI PENCEGAHAN FRAUD DANA KAPITASI PUSKESMAS DI KOTA SEMARANG - Setiaji, Tomi Konstantia; Jati, Sutopo Patria; Arso, Septo Pawelas (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
National Health Insurance Programme (JKN) is part of National Social Insurance System (SJSN) which is held by mandatory social health insurance based on regulation number 40 year 2004. JKN programme in giving service is implementing hierarchy system by using herarchy referral pattern which is started from primary service which consist of community health center (puskesmas), doctor clinic, and primary clinic to tertiary service. JKN fraud projection is 5-10% or equal to Rp 1,8 trillion – Rp 3,6 trillion, based on BPJS premi prediction 2014. Community health center (puskesmas) as gatekeeper has capitation funding based on JKN participatory number in these area. Semarang is one of big city in Indonesia, has Rp 24.884.142.000 total community health centers capitation funding in 2014. This research is purposed to predict the potency of capitation funding fraud in community health center and compose strategy to prevent fraud by using SWOT analysis from internal and external factors of capitation funding organizer of community health centers in Semarang. This research is qualitative research with indepth interview method wich is conducted with stakeholders who are in charge with fraud prevention of capitation funding fraud in community health centers in Semarang. The result shows that potency of capitation funding fraud in community health center is triggered by new implemented program and regulation which is not clearly mention the usage of community health center capitation funding and human resources as capitation funding organizer of community health centers organizer. To solve this problem, Semarang must has strategy based on strength, weakness, opportunity, and threat to prevent fraud of puskesmas funding capital.